Beyond surface redox and oxygen mobility at pd-polar ceria (100) interface: Underlying principle for strong metal-support interactions in green catalysis - Mahadi, AH; Ye, L; Fairclough, SM; Qu, J; Wu, S; Chen, W; Papaioannou, EI; Ray, B; Pennycook, TJ; Haigh, SJ; Young, NP; Tedsree, K; et al. (Elsevier, 2020)
When ceria is used as a support for many redox catalysis involved in green catalysis, it is well-known that the overlying noble metal can gain access to a significant quantity of oxygen atoms with high mobility and fast reduction and oxidation properties under mild conditions. However, it is as yet unclear what the underlying principle and the nature of the ceria surface involved are. By using two tailored morphologies of ceria nanocrystals, namely cubes and rods, it is demonstrated from Scanning Transmission Electron Microscopy with Electron Energy Loss Spectroscopy (STEM-EELS) mapping and Pulse Isotopic Exchange (PIE) that ceria nanocubes terminated with a polar surface (100) can give access to more than the top most layer of surface oxygen atoms. Also, they give higher oxygen mobility than ceria nanorods with a non-polar facet of (110). A new insight for the possible additional role of polar ceria surface plays in the oxygen mobility is obtained from Density Functional Theory (DFT) calculations which suggest that the (100) surface sites that has more than half-filled O on same plane can drive oxygen atoms to oxidise adsorbate(s) on Pd due to the strong electrostatic repulsion.